The Implementation of Cooperative Learning to enhance Religious and Moral Values In Early Childhood - Nenci Tefi; Yunita Raikou; Eunike laa; Yandi Failed; Yulinda Yulinda; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Background: Religious and moral development is a fundamental aspect of early childhood education because it shapes children's character, values, and positive behaviour through meaningful learning experiences. Objective: This study aimed to examine the relationship between the implementation of the Cooperative Learning model and the religious and moral development of children aged 5–6 years at Cemara Liliba Kindergarten, Kupang City. Method: This quantitative study employed an ex post facto design involving 22 children selected through total sampling. Data were collected using structured observation instruments assessing Cooperative Learning implementation and children's religious and moral development. Descriptive statistics and simple linear regression were performed using SPSS version 25. Results: The descriptive findings indicated that most children demonstrated moderate to high levels of Cooperative Learning participation and religious and moral development. However, regression analysis revealed no statistically significant relationship between Cooperative Learning and children's religious and moral development (p = 0.353 > 0.05). The coefficient of determination (R² = 0.043) showed that Cooperative Learning explained 4.3% of the variance, while 95.7% was attributable to other factors beyond the scope of this study. Novelty: This study provides empirical evidence regarding the implementation of Cooperative Learning in an authentic early childhood classroom while highlighting the limited contribution of classroom learning alone to children's religious and moral development. Conclusion: Cooperative Learning creates meaningful, collaborative, and enjoyable learning experiences; however, strengthening children's religious and moral values requires continuous support through teacher modelling, parental involvement, and consistent moral habituation.